RIG-I and TLR-7/8 agonists as combination adjuvant shapes unique antibody and cellular vaccine responses to seasonal influenza vaccine - Jangra, Sonia; Laghlali, Gabriel; Choi, Angela; Rathnasinghe, Raveen; Chen, Yong; Yildiz, Soner; Coughlan, Lynda; García-Sastre, Adolfo; De Geest, Bruno G.; Schotsaert, Michael (Frontiers in Immunology, 2022)
Influenza vaccine effectiveness could be improved by combination with an adjuvant with the potential to enhance the host-vaccine response both quantitatively and qualitatively. The goal of this study was to explore a RIG-I agonist (SDI-nanogel) and a TLR7/8 agonist (Imidazoquinoline (IMDQ)‐PEG‐Chol) as adjuvants, when co-administered with a licenced quadrivalent inactivated influenza vaccine (QIV), and to determine the role of these adjuvants in directing helper T (Th) cell responses for their role in the immunoglobulin (Ig) class switching. Administration of QIV with the two adjuvants, individually or combined, resulted in enhanced HA-specific serum ELISA IgG titers, serum hemagglutination inhibition (HAI) titers and splenic T cell responses as examined by IFN-γ and IL-4 enzyme-linked immunosorbent spot (ELISPOT) assays, 4-weeks post-prime and post-boost vaccination in BALB/c mice. While QIV+SDI-nanogel largely induced antigen-specific IgG1 responses, QIV+IMDQ-PEG-Chol predominantly induced IgG2a antibody isotypes post-prime vaccination, suggesting efficient induction of Th2 (IL-4) and Th1 (IFN-γ) responses, respectively. Combination of the two adjuvants not only skewed the response completely towards IgG2a, but also resulted in induction of HAI titers that outperformed groups that received single adjuvant. Moreover, enhanced IgG2a titers correlate with antibody-mediated cellular cytotoxicity (ADCC) that targets both the highly conserved H1 hemagglutination (HA) stalk domain and N1 neuraminidase (NA). A booster vaccination with QIV+IMDQ-PEG-Chol resulted in a more balanced IgG1/IgG2a response in animals primed with QIV+IMDQ-PEG-Chol but increased only IgG2a titers in animals that received the combination adjuvant during prime vaccination, suggesting that class switching events in germinal centres during the prime vaccination contribute to the outcome of booster vaccination. Importantly, IMDQ-PEG-Chol, alone or in combination, always outperformed the oil-in-water control adjuvant Addavax. Vaccine-induced antibody and T cell responses correlated with protection against lethal influenza virus infection. This study details the benefit of adjuvants that target multiple innate immune receptors to shape the host vaccine response.